Classic sports massage vs. Chinese self-massage. Which one is more effective in warm-up? - Boguszewski Dariusz; Adamczyk Jakub Grzegorz; Hanc Aleksandra; Szymańska Agata; Chełchowska Sylwia; Białoszewski Dariusz (Sciendo, 2021)
Study aim: Warm-up is an indispensable element of sports training. The aim of the study was to determine the effect of warm-up exercises with Swedish, classic sports massage and Chinese self-massage on functional limitations of the locomotive system.